Binding of a viral IRES to the 40S subunit occurs in two successive steps mediated by eS25. Issue 14 (1st July 2020) - Walters, Beth; Axhemi, Armend; Jankowsky, Eckhard; Thompson, Sunnie R
Abstract: The mechanism for how internal ribosome entry sites (IRESs) recruit ribosomes to initiate translation of an mRNA is not completely understood. We investigated how a 40S subunit was recruited by the cricket paralysis virus intergenic region (CrPV IGR) IRES to form a stable 40S–IRES complex. Kinetic binding studies revealed that formation of the complex between the CrPV IGR and the 40S subunit consisted of two-steps: an initial fast binding step of the IRES to the 40S ribosomal subunit, followed by a slow unimolecular reaction consistent with a conformational change that stabilized the complex. We further showed that the ribosomal protein S25 (eS25), which is required by functionally and structurally diverse IRESs, impacts both steps of the complex formation. Mutations in eS25 that reduced CrPV IGR IRES activity either decreased 40S–IRES complex formation, or increased the rate of the conformational change that was required to form a stable 40S–IRES complex. Our data are consistent with a model in which eS25 facilitates initial binding of the CrPV IGR IRES to the 40S while ensuring that the conformational change stabilizing the 40S–IRES complex does not occur prematurely.